Coronary Angiography in Dilated Cardiomyopathy Patients Presenting to Cardiac Hospital at Lumbini Province Nepal - Gautam, Samir; Dhungel, Sachin; KC, Bishal; Panjiyar, Rajesh (Journal of Universal College of Medical Sciences, 2023)
INTRODUCTION Dilated cardiomyopathy is one of the common cause of patients presenting with symptoms of heart failure. It is often treated as respiratory disease in the absence of speciﬁc evaluation. We wanted to evaluate the presence of coronary artery disease in dilated cardiomyopathy patients. MATERIAL AND METHODS It was a prospective observational study conducted at Gautam Buddha Community Heart Hospital. One hundred sixty patients with the diagnosis of dilated cardiomyopathy were evaluated with coronary angiography. RESULTS Distribution of patients was males 68.1% and females 31.9%. Most patients (61.2%) were in the age group 45 to 65 years. Dyspnea (80.6%), fatigue (25%), cough (20%), chest discomfort (16.9%), edema (15%) and palpitation (11.9%) were common symptoms. Majority of patients were smoker 41.9%. Coronary artery disease was found in 44.4% with signiﬁcant stenosis in 36.3%. Among the patients with signiﬁcant coronary artery stenosis two vessel disease was present in 54%, one vessel disease in 32% and three vessel disease in 14%. CONCLUSION Coronary artery disease was frequently present in dilated cardiomyopathy patients. Optimization of management becomes easier with thorough evaluation of DCM patients including coronary angiography.